A Comprehensive Study on Gamma Rays and Fast Neutron Sensing Properties of GAGOC and CMO Scintillators for Shielding Radiation Applications. (26th September 2017) - Issa, Shams A. M.; Sayyed, M. I.; Zaid, M. H. M.; Matori, K. A.
Abstract : The WinXCom program has been used to calculate the mass attenuation coefficients ( μm ), effective atomic numbers ( Z eff ), effective electron densities ( N el ), half-value layer (HVL), and mean free path (MFP) in the energy range 1 keV–100 GeV for Gd3 Al2 Ga3 O12 Ce (GAGOC) and CaMoO4 (CMO) scintillator materials. The geometrical progression (G-P) method has been used to compute the exposure buildup factors (EBF) and gamma ray energy absorption (EABF) in the photon energy range 0.015–15 MeV and up to a 40 penetration depth (mfp). In addition, the values of the removal cross section for a fast neutron ∑ R have been calculated. The computed data observes that GAGOC showed excellent γ -rays and neutrons sensing a response in the broad energy range. This work could be useful for nuclear radiation sensors, detectors, nuclear medicine applications (medical imaging and mammography), nuclear engineering, and space technology.